Mengembangkan Potensi Masyarakat Bidang Sosial Melalui Pemasaran dan Meningkatkan Sumber Daya Manusia di Desa Alai - Hesti Ifititah Sari; Shafiera Lazuarni; Lukita Tripermata; Roswaty Roswaty (Universitas Islam Kadiri, 2022)
The absence of optimizing the potential of the community of Alai Village, Lembak District, Muaro Enim Regency in the social field is the background for the KKN work program of the Faculty of Economics, Indo Global Mandiri University to optimize community potential through marketing and improving human resources. Marketing strategy is the process of leading an organization/company to key market opportunities, increasing sales and generating desired profits. Marketing strategy is also an important tool for a company to win the competition. Business people tend to think that competitors are nothing more than threats, but in reality, competitors help companies improve their creativity and performance, innovate efficiently and effectively, and become world-class companies. Digital marketing is one of the most influential marketing media. In this case, by using digital marketing through social media, Alai Village SMEs can market their domestic industrial products. This study proposes a digital marketing strategy for MSME products using social media. The results of this survey show that the social media of choice are WhatsApp, Instagram and Shopee. These media are more efficient vehicles for spreading the news.